Struktur Sosial Keberagaman Pemeluk Islam di Indonesia - Abdul Munir Mulkhan (Al-Jami'ah: Journal of Islamic Studies, 2001)
All religions, in accordance with their experiences, bring many religious schools and patterns of their adherents. It appears on institutional in the form of organization such as Muhammadiyah and Nahdlatul Ulama (NU) with its religious patterns. By means of similar probes, the Islamic adherents in Indonesia can be differentiated into two big modes, santri and abangan. Up to now both always give character to Islamic relationship and national reality with the shape of different party. The Islamic variations are forms of the religious meaning by its adherent differently conforming with his couscous’s structure. The experience of life, education, job and family give big influence whether Islam is known, to be conscious and meant by every adherent. In social realities of its adherent, Islam gives many meanings, schools and behavioral patterns that can be opposite one another. The Islamic realities can be explained, researched and understood from its social dynamic adherent. The experts of socials sciences observe such social Islamic reality as a function of dialectic relationship of a single textual teaching and the reality of its dynamic adherent. Hence, it can be understood that the sufism develops in one area and the teaching of syariah is more accepted in other areas.Most of farmers and labors living in villages tend to follow magic known as abangan. The others are santri who obey syariah and some of them are more ethical in their religion. The understanding of Islam in its social reality is important to be developed to measure the scale of Islamic acceptance in an area. Such research can give information on Islamic elements that base way of life from most people, and elements that have not been widely acceptend. IAIN can prepare the policy of education based on Islamic social reality, while Islamic organization prepares strategy for needs of community and nation or to widen its organization.